CLOUD COMPUTING SECURITY CHALLENGES - NARENDRA RAO TADAPANENI (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper explores security challenges faced by cloud computing. It discusses the prevailing protection tactics to secure the cloud infrastructure, programs and drawbacks. Cloud computing started in the mid 90’s and one of its earlier users are Amazon and Ali Baba. It is growing really fast in the field of computer science. People nowadays are using cloud computing at a very vast level. Cloud computing is basically based on the Internet and has the most powerful architecture of computation. After a particular has deployed his/her cloud based platform, the biggest fear is its security. A cloud as mentioned earlier is all web-based which means that retrieving data from a particular cloud isn’t something impossible. As the use of cloud computing is growing, so are the security challenges. More people are getting aware of the technology which is making it easier for them to break into different clouds and retrieve their desired information. Many organizations have started offering cloud based solutions to their customers which has made security a major aim in their projects. On the other hand, many security experts are working on finding better security solutions. Even though security is getting better day by day but still hackers are finding ways to exploit a particular cloud. The Cloud security concern becomes more complex below the cloud model as many other fields continuously enter the Cloud computing industry.